Stochastic Model Predictive Control for Hybrid Energy Systems - Gienger, A; Sachs, J.; Sawodny, O. (Электронное моделирование, 2017)
Microgrids are a promising approach for the integration of renewable energy sources in existing networks and the energy supply of rural areas. A cost effective option for a microgrid is given by a hybrid energy system, which combines e.g. diesel generators, photovoltaic panels and batteries as considered in this paper. However, the interaction of the components and uncertainties in the load demand and photovoltaic power make the controller design challenging. This paper discusses a Stochastic Model Predictive Control approach which yields promising results regarding effectiveness and reliability as shown in a simulation study. Использование электроэнергетических микрогрид-систем является перспективным подходом к интеграции возобновляемых источников в существующие сети и энергообеспечение сельской местности. Экономическая эффективность электроэнергетических микрогрид-систем зависит от гибридной энергосистемы, объединяющей дизельные генераторы, фотоэлектрические панели и батареи. Однако взаимодействие составляющих и неопределенность графика нагрузки и фотоэлектрической энергии обусловливают необходимость создания блока управления. Рассмотрено применение стохастической модели для интеллектуального управления, что позволит обеспечить эффективность и надежность энергосистемы.